INVERSE VARIATIONAL INEQUALITIES AND SECOND-ORDER DYNAMICAL SYSTEMS - Quoc Thanh Trinh (Tạp chí Khoa học Đại học Đà Lạt)
We consider the inverse variational inequality problem in finite-dimensional space and study its associated second-order dynamical system. In particular, we propose a second-order dynamical system whose trajectory converges exponentially to the solution of the inverse variational inequality problem under the Lipschitz continuous and strongly monotone condition.